Pelestarian Alat Musik Beghu Sebagai Ikon Kabupaten Nagakeko Flores Nusa Tenggara Timur - Fikri, Kanzul; Samino, Sena (Universitas Negeri Surabaya, 2025)
The preservation of local culture in Indonesia faces serious challenges, both from within the community and due to the influence of globalization. This article focuses on the study of the traditional Beghu musical instrument from Nagekeo Regency, East Nusa Tenggara, as a representation of intangible cultural heritage that is rich in historical, educational, and artistic value. This study uses a descriptive qualitative approach with purposive sampling and snowball sampling techniques to explore the meaning, function, and challenges in the preservation of Beghu. The results show that Beghu not only plays an important role in the traditional rituals and social life of the community, but also faces real threats due to lack of documentation, lack of interest from the younger generation, and limited institutional support. These findings confirm the importance of integrating traditional musical instruments in education and strengthening local communities through documentation, training, and cultural activities. Structured and collaborative preservation efforts are needed to keep Beghu alive as a symbol of the identity and cultural pride of the Nagekeo people.